Pola Komunikasi Guru Dalam Mengajarkan Aksara Simalungun di SD 094126 Naga Dolok - Indriani, Pitri (Universitas Muhammadiyah Sumatera Utara, 2024)
Teachers act as educators in schools, tasked with providing knowledge, abilities and values to students and guiding them in the learning process. Communication is an important process in teaching and learning, where teachers must choose effective learning media to manage interactions with students. Local wisdom-based education requires a process of collecting and applying local wisdom in learning, such as the Simalungun script in the context of Batak culture. Based on this, the formulation of the problem to be studied in this thesis is, namely, what is the teacher's communication pattern in providing local language learning with Simalungun script to students at SD 094126 who live in a scope or environment where the majority are Javanese. The aim of this research is to find out how teachers teach knowledge of local wisdom, cultural language, Simalungun script to elementary school students. The data collection technique in this research is data based on the results of observations, interviews and documentation. The data analysis technique in this research uses interactive analysis. As a result of the research conducted by researchers, researchers found that the form of communication used was communication intensity in the form of communication frequency and communication duration as well as using one-way communication and two-way communication.